Identification of MERS-CoV in dromedary camels - Ferguson, Neil M; Van Kerkhove, Maria D (The Lancet infectious diseases, 2014)
A multidisciplinary team of scientists from the Netherlands, Qatar, and the UK report the first definitive isolation of the Middle East respiratory syndrome coronavirus (MERS-CoV) in a non-human animal species, dromedary camels.1 Phylogenetic analysis of the 4·2 kb partial viral sequence obtained from one animal show the virus to be almost identical to isolates obtained from two human cases who had had contact with the camels on the affected farm. The affected smallholding is part of a much larger farm complex located about 30 km northwest of Doha, Qatar, which has been the subject of intensive epidemiological investigation since the diagnosis of the first human case on the farm 2 months ago.2 Although the virus has only been sequenced from one camel to date, some virological evidence of infection was reported in 11 of 14 camels on the farm, and serological evidence of exposure to a MERS-CoV-like virus was noted in all of them.